Aggregates. Definition and modelization - Lapo Ghiringhelli (JLIS.it, 2020)
The paper aims to illustrate the nature and modeling of aggregates, whose understanding was a slow process. Aggregates, due to the complexity of their modeling, were only briefly discussed in the conceptual model Functional Requirements for Bibliographic Records. The Working Group on Aggregates represents the most in-depth examination attempt; the Final Report of 2011 deserves credit for giving a clear definition of aggregate and distinguishing three types, proposing a modeling consistent with FRBR. The IFLA Library Reference Model incorporates the results of the Working Group and expands on certain aspects. Particularly worthy of mention, the model offers a solution for modeling serials, the type of aggregates that presents some peculiarities and complexities.